"At Home Too Everything Is Falling Apart": Waste, Domestic Disorder, and Gender in Alison Lurie's Early Fiction. (28th September 2017) - DINI, RACHELE
Abstract : This paper examines the gendered aspects of consumer waste, dirt, and domestic mess in three early novels by Alison Lurie – Love and Friendship (1962), The Nowhere City (1965), and The War between the Tates (1974), set in 1969 – which I argue provide an incisive account of the transformation of gender relations over the course of the 1950s and 1960s. By focussing on the signifying potential of material objects in these texts, I seek to demonstrate Lurie's relevance to the "thingly turn" in literary criticism, to reignite interest in an author whose work has received surprisingly little scholarly attention, and to instigate a wider discussion of waste in her work as a whole, where it in fact proliferates. In broader terms, I hope to complicate existing scholarship on waste in literature (including my own in this area to date), which remains almost exclusively focussed on male authors.